Access to Maternal Healthcare and Reduction of Maternal Mortality in Plateau State, Nigeria - Magaji Jummai MUSA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
Maternal mortality remains a pressing public health concern in Nigeria, with the country accounting for one of the highest maternal death rates globally. Despite global and national commitments to reduce maternal mortality, access to quality maternal healthcare services is still inadequate, particularly in rural and low-resource settings. This study examined the implications of access to maternal healthcare services on reducing maternal mortality in Plateau State, using Andersen’s Behavioural Model of Health Service Use as the guiding framework. A cross-sectional survey design was adopted, and the Taro Yamane formula was applied to determine a sample size of 400 women of reproductive age from a population of 120,000. Data were collected through structured questionnaire and key informant interviews with healthcare providers. Quantitative data were analysed using SPSS version 26, while qualitative findings were thematically organized. The results revealed that although awareness of antenatal and delivery services was high, barriers such as financial constraints, long distances, shortage of skilled personnel, cultural beliefs, and poor infrastructure significantly reduced access to maternal healthcare. The study concludes that socio-economic, cultural, and systemic barriers undermine maternal health outcomes. Thus, it recommends expanding primary healthcare coverage, strengthening community-based insurance, and promoting culturally sensitive maternal health education to enhance access to quality maternal healthcare services and reduce maternal mortality in Plateau State, Nigeria.